Flame morphology of horizontal jets under sub-atmospheric pressures: Experiment, dimensional analysis and an integral model. (1st January 2022) - Lv, Jiang; Zhang, Xiaolei; Liu, Shixiang; Lu, Hongyu; Ma, Yuxuan; Hu, Longhua
Highlights: Flame morphologic characteristics under various atmospheric pressures quantified. Effect of sub-atmospheric pressure on horizontal jet flame behavior revealed. The characteristic length scale for flame morphology proposed. Correlations of flame horizontal projection length and vertical height established. An integral model for the conservation of mass and momentum developed. Abstract: This paper investigated the flame morphology including horizontal projection length and vertical height of horizontal turbulent jets under various sub-atmospheric pressures, for which both data and model are few. Experiments are conducted for various nozzle diameters in the range of 3 mm to 7 mm. Propane is used as the fuel in this study. The sub-atmospheric pressures, created by a reduced pressure chamber, are varied from 40 kPa to 100 kPa. A digital video camera is used to measure the flame morphologic characteristics. The experimental results show that the flame horizontal projection length increases with the increasing of heat release rate or the decreasing of chamber pressure. Meanwhile, the flame vertical height first increases then decreases with the increasing of heat release rate or the decreasing of chamber pressure, which shows a non-monotonic behavior. A characteristic length scale is proposed by dimensional analysis considering jet initial momentum, flame buoyancy and ambient air density to illustrate the controlling mechanisms in the flow development. And the characteristic air entrainment flow rate ρ ∞ L m 2 g ′ L m is used to normalize the stoichiometric mass flow rate at the flame tip, which determines the total length of the trajectory. Non-dimensional formulas are developed based on the derived length scale and characteristic air entrainment flow rate to describe the flame horizontal projection length and vertical height of horizontal jets under various sub-atmospheric pressures. Finally, an integral model considering air entrainment mechanism, top hat profiles and strong plume theory for the conservation of mass and momentum in horizontal and vertical directions is developed, which shows to describe the flame morphologic characteristics well.